2006
DOI: 10.1007/s10103-006-0380-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy in management of postmastectomy lymphedema

Abstract: The aim of this paper was to study the effects of low-level laser therapy (LLLT) in the treatment of postmastectomy lymphedema. Eleven women with unilateral postmastectomy lymphedema were enrolled in a double-blind controlled trial. Patients were randomly assigned to laser and sham groups and received laser or placebo irradiation (Ga-As laser device with a wavelength of 890 nm and fluence of 1.5 J/cm2) over the arm and axillary areas. Changes in patients' limb circumference, pain score, range of motion, heavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
107
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 16 publications
0
107
1
1
Order By: Relevance
“…Lymphedema onset is a stressful, lifealtering event [1]. Breast cancer survivors with lymphedema report a poorer quality of life (QOL) than those without lymphedema and have multiple health-related symptoms [9,15,17,24].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphedema onset is a stressful, lifealtering event [1]. Breast cancer survivors with lymphedema report a poorer quality of life (QOL) than those without lymphedema and have multiple health-related symptoms [9,15,17,24].…”
Section: Introductionmentioning
confidence: 99%
“…These therapies include complex physical therapies, manual lymphatic drainage, compression banding and garments, pneumatic pump therapies, elevation, exercise, and low-level laser therapy (LLLT) [7]. LLLT has been used in the treatment of postmastectomy lymphedema since 1995 [8][9][10][11] in countries other than the US and it was approved by FDA in 2007. It is presumed that by increasing lymphatic flow, LLLT reduces the surplus of both tissue protein and fluid, and thereby improves limb performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is presumed that by increasing lymphatic flow, LLLT reduces the surplus of both tissue protein and fluid, and thereby improves limb performance [9]. It has been suggested that LLLT encourages lymphangiogenesis and stimulates lymphatic motoricity thus the greatest benefit is achieved over a long period of time [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Compression therapy uses a functional compression garment or bandage 2,3) . Previous studies suggest that compression therapy is effective at reducing the circumference of edema 4) ; therefore, it is clinically useful for patients with diseases such as lymphoma, venous ulcer, and deep vein thrombosis. A secondary effect of compression therapy is an improvement in the quality of life 5) .…”
Section: Introductionmentioning
confidence: 99%